Predictive value of a modified classification of fallopian tube status on prognosis of tubal factor infertility after laparoscopic surgery. Issue 13 (March 2019) - Yuan, Lin; Jingying, Huang; Xiujuan, Chen; Chengying, Lian; Xiaochen, Huang; Xiumei, Xiong; Yulong, Zhang; Zihua, Chen
Abstract : Abstract: Built on 2 existing classification systems, this study was to develop a new classification system to better predict the pregnancy prognosis after laparoscopic surgery in patients with tubal factor infertility and accordingly propose a management strategy. We followed up 423 patients suffering from tubal factor infertility who had undergone hysteroscopic-laparoscopic surgery for 2 years without in vitro fertilization and embryo transfer (IVF/ET). Based on the operative reports, a new, modified classification of fallopian tube status (hereafter referred to as the modified classification) was developed with reference to the 2 existing classification systems (the r-AFS classification of pelvic adhesions and the scoring system of distal tubal obstruction). A score of 0 to 3 was assigned to each of the 4 factors (tubal wall consistency, hydrosalpinx, pelvic adhesions, and tubal patency) for each of the tubes with a total bilateral score of 0 to 24. The patients were classified for the abnormalities of the fallopian tubes into 3 groups: mild (<8), moderate (8–15) and severe (>15). By utilizing SPSS 20.0 Statistic Analysis Software, the data were analyzed with t test, Chi-Square test, ANOVA or ROC as appropriate. Each of the 4 factors of the modified classification was independently and closely associated with post-surgical prognosis ( P  < .05). There was a statistically significant difference in postoperative pregnancy prognosis among the 3 groups of patients ( P  < .05). Patients with a score of <8 (mild) had the highest intrauterine pregnancy rate, reaching 60.1%. In contrast, patients with a score of 8 to 15 (moderate) had a significant increase in ectopic pregnancy (21.5%), while patients with a score of >15 (severe) had a significantly increased infertility rate of 89.5%. When the pregnancy outcomes were divided into intrauterine pregnancy and other outcomes, the modified classification had the largest area under the ROC curve (0.569) ( P  < .05). With the optimum cutoff of 4.5, the sensitivity was 88.6%, specificity was 74.5% and accuracy was 63.1%. The modified classification of fallopian tube status is a simple and practical scoring system which can comprehensively and effectively evaluate the function of the fallopian tube and thus is more accurate than the other 2 systems in predicting the postoperative pregnancy outcomes.